Characterization of the genetic environment of the bla KPC-2 gene among Klebsiella pneumoniae isolates from a Chinese Hospital - Shen,Pinghua (2016)
Abstract Infection caused by carbapenem-resistant Klebsiella pneumoniae has become a major healthcare threat and KPC-2 enzyme is a dominant factor mediating carbapenems resistance in K. pneumoniae. This study was designed to determine the genetic environment of bla KPC-2, which prevailed in clinical K. pneumoniae isolates recovered in Huashan Hospital, Shanghai, China. Forty-two clinical isolates were included in this study by bla KPC-2 screening. After multilocus sequence typing and plasmid analyses of PCR-based replicon typing (PBRT), junction PCR, mapping PCR and crossing PCR assays, primer walking, and amplicon sequencing were used to analyze the genetic environment of the bla KPC-2 gene. ST423, ST65, ST977, and ST11 were all detected in KPC-2-producing K. pneumoniae. Two types of bla KPC-2-bearing genetic structure were found: Tn1721-bla KPC-2-Tn3 and Tn1721-bla KPC-2-ΔTn3-IS26; and were carried in IncX and IncFII plasmids, respectively. In conclusion, the genetic environment of the bla KPC-2 gene was diverse and Tn1721-bla KPC-2-ΔTn3-IS26 was dominant in clinical K. pneumoniae isolates in Huashan Hospital. This study sheds some light on the genetic environment and should foster further studies about the mechanism of the bla KPC-2 dissemination.